Anti-diabetic activity of extracts and a bioactive compound isolated from Hypoxis hemerocallidea (Hypoxidaceae) in a murine model of spontaneous diabetes - Naidoo, Vinny (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.